The Influence of Celebrity Endorsement in Instagram towards Customer Behavior and Purchase Intention in Healthy Food Diet Business - Rendika Nugraha; Kunthi A. Kusumawardani; Vinda Octavianie (FIRM Journal of Management Studies, 2018)
Healthy life style has become a choice in the society especially in the big city where people tend to aware about the importance of consuming healthy food and implement healthy life style. This condition has a positive impact for those who run the business in food and beverage business especially with healthy food approach. Nowadays, smartphone or tablet already becomes part of people life that cannot be separated in daily activity. Driven by healthy life style and technological life style, 3 Skinny Minnies appears to be one of the player in providing healthy food to its customer and utilizing social media as distribution channel such as Instagram to promote their product. In promoting healthy life style by providing healthy food, 3 Skinny Minnies consistently utilize celebrity endorsement to become content of Instagram feeds. This research analyzes the effectiveness of celebrity as endorser in influencing purchase intention by attitude toward the brand using quantitative approach which, the primary data were collected from the respondents through online questionnaire. There were 274 respondents as a sample size of the research and through validity and reliability analysis that processed by statistical software using factor analysis and structural equation modeling. Based on the data analysis, it is found that celebrity endorsement has low influence on purchase intention even though the attitude toward the brand has significantly influence the customer. Hence, attitude toward the brand in this case has a direct influence on purchase intention. Thus, in order to win the competition, it is important to improve the way 3 Skinny Movies in promoting the products, so that the activities will be more effective in generating revenue.